Resilience and Transpersonal Psychology: enhancing values, action and spirituality - Manoel José Pereira Simão; Vera Saldanha (O Mundo da Saúde)
We see more and more news in the media about increasing cases of violence in robberies, murders, crimes and corruption. Society passes through a revision of values where education and discipline for caring for humans use several theses aiming to discover efficient ways and tools for promoting a culture of peace based on values. Integral health promotion and the construction of a stronger community based on humane actions and human values may be favored by programs and projects based on a Transpersonal approach that revalues the importance of transcendence and spirituality inherent to human psyche. Many researches in this field are based on the question: How people exposed to risky situations and experiences harmful for their development are able to adjust to daily demands? The proposal of this article is to understand the grounds of transpersonal psychology integrative approach (Saldanha 2006) and its application for strengthening resilience mechanisms in human groups in general and groups of patient in a psychology clinic. For doing this we present the concepts on resilience and after mention the main bases of transpersonality applied to the development of human values and integration of spirituality to human condition and health.